Pemanfaatan Lubang Bekas Tambang Sebagai Danau Pascatambang di PT Kasongan Bumi Kencana Kabupaten Katingan Provinsi Kalimantan Tengah - I Putu Putrawiyanta (PROMINE, 2020)
Open pit mining will create a change in the environment and leave a former mine (void). A void that is left at the end of mining activities without any utilization planning could potentially cause an unwanted impact on the environment. The final hue of the mines in this study is limited to land allocation, and surface water quality. The research aims to assess the use of a former mine (void) for sustainable development. The results of this research show that the former mine (void) could potentially contribute to sustainable development. The community empowerment Program around the mine in utilizing the former mine holes is crucial for the continuity of the local economic drive. The quality of mine wastewater released to water or river bodies and the quality of surface water in a former mine (void) becomes a representation of the danger of the use of water for human health.